Changing rates but persisting seasons: patterns of enterovirus infections in hospitalizations and outpatient visits in Denmark 2015-2022 - Johannesen, Caroline Klint; Egeskov-Cavling, Amanda Marie; Jepsen, Micha Phill Grønholm; Lange, Theis; Krause, Tyra Grove; Nygaard, Ulrikka; Fischer, Thea K. (Frontiers in Virology, 2024)
Background: Enteroviruses (EV) constitute a diverse group of viruses manifesting a broad spectrum of clinical presentations in humans ranging from mild skin manifestations to more severe central nervous system (CNS) infection. Severe infections are reported with increased frequency globally, albeit the burden of diseases and the evolution of circulating viruses is largely unknown. We aimed to systematically explore contemporary trends in hospitalizations attributed to EV infections using national hospitalization discharge data.We utilized the Danish National Patient Register which holds information on all contacts to Danish hospitals. We covered eight full years (2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022). Length-of-stay and administrative procedure codes were used to distinguish hospital admissions from outpatient visits. We utilized burden of disease estimates and distribution statistics.We identified 1029 hospitalizations and 1970 outpatient visits due to EV infections. The hospital admissions were primarily associated with CNS-infections (n=570, 55.4%) and skin (n=252, 24.5%), with variation over the studied period. The admitted patients were predominately children (43.8%) though patients were identified in all ages. The clinical manifestation was associated with age, with CNS infections dominating in the neonates and adults, and skin infections dominating in children 1-2 years (17.2%). Outpatient visits were predominantly observed amongst children 1-2 years (55.0%), presenting with skin symptoms (77.9%). We show a seasonal pattern of EV infections with summer/fall peaks and markedly impact on the EV hospitalization burden related to COVID- mitigation measures including national lockdown periods. 25% of hospital admissions occurred during 2020-2022.EV infections caused both hospital admissions and outpatient visits in the period studied, predominately amongst children aged 1-2 years. Overall, skin infections dominated the outpatient visits, while the majority of hospital admissions were due to CNS infections. The pandemic period did not change the seasonal pattern of EV infections but notably lowered the number of admissions to hospital with CNS infection and raised the number of outpatient admissions with skin infection.